Improving Student Learning Activity Through the Application of Problem-Based Learning and Culturally Responsive Teaching Approaches - Matondang, Indrawani; Non Shamdas, Gamar Binti; Jihad, Jihad (International Journal on Advanced Science, Education, and Religion, 2025)
Student engagement is a crucial indicator of the success of the learning process. Engagement is demonstrated not only through physical involvement, such as participating in discussions, asking questions, or answering questions, but also through mental engagement in understanding and reflecting on the material. However, in practice, many students still exhibit low levels of engagement, resulting in learning that tends to be one-way and suboptimal. This low engagement can result in a lack of learning motivation, weak critical thinking skills, and poor overall learning outcomes. This study aims to improve student engagement through the application of the Problem-Based Learning (PBL) model combined with the Culturally Responsive Teaching (CRT) approach. The method used was Classroom Action Research (CAR), conducted over two cycles, with students of grade X-C at SMANOR Tadulako Palu as subjects. The research instrument was an engagement observation sheet, while data analysis was descriptive to describe the level of student engagement from cycle to cycle. The results showed an increase in student engagement. In cycle I, the average student engagement rate was only 58.71%, which is considered moderate. After improvements were made to the learning process in cycle II, the engagement rate increased to 75.75%, which is considered good. This improvement occurred because the PBL model enabled students to be more active in problem-solving, while the CRT approach made learning more relevant to their cultural context. Thus, it can be concluded that the combination of PBL and CRT has proven effective in creating a contextual, collaborative, and student-centered learning environment. This model is able to increase student motivation, self-confidence, and engagement in Biology learning.